2023
DOI: 10.56093/ijans.v93i1.120089
|View full text |Cite
|
Sign up to set email alerts
|

Genetic study of important economic traits in Hariana cattle

Abstract: The present investigation was undertaken to access first lactation total milk yield, first lactation length, productive life, herd life and total life. Breeding information were used from the history sheet registers and herd inventory registers of Hariana cattle maintained at DUVASU farm, Mathura and Babugarh farm, Hapur. The data of productive animals with date of calving from 1966 to 2018 and date of birth from 1962 to 2013 were collected for the study. The overall averages for FLTMY, FLL, PL, HL and TL were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
(15 reference statements)
6
1
1
1
Order By: Relevance
“…The heritability estimates for combined sire and dam components were 0.277 ± 0.110, 0.307 ± 0.113, 0.391 ± 0.120 for egg production up to 40, 52 and 64 weeks of age. Similar values for EP 40 were reported in IWK [39]. Lower heritability estimates than the present study was reported by some authors [32,35,40], whereas higher heritability values were obtained in RIR [41].…”
Section: Genetic Parameterssupporting
confidence: 90%
See 3 more Smart Citations
“…The heritability estimates for combined sire and dam components were 0.277 ± 0.110, 0.307 ± 0.113, 0.391 ± 0.120 for egg production up to 40, 52 and 64 weeks of age. Similar values for EP 40 were reported in IWK [39]. Lower heritability estimates than the present study was reported by some authors [32,35,40], whereas higher heritability values were obtained in RIR [41].…”
Section: Genetic Parameterssupporting
confidence: 90%
“…The heritability estimates for egg production up to 52 weeks was in close agreement with estimates reported by authors [31,35,42], while heritability estimates for EP 64 were found to be higher when compared with values in Naked Neck chicken [13]. Egg weights exhibited moderate heritability ranging from 0.459 ± 0.14 to 0.575 ± 0.15 and these values were found to be in a closer range reported in white leghorn control [38,39] while other authors reported lower value than the present study. Variations in egg weight may be due to breed differences, type of birds and bodyweight of birds [35].…”
Section: Genetic Parameterssupporting
confidence: 89%
See 2 more Smart Citations
“…Ключевые слова: корова, возраст первого отёла, молочная продуктивность, ген OLR1, DGAT1, LEP. на подготовку коров до продуктивной жизни, увеличивает ежегодный генетический прирост и увеличивает среднюю продуктивную жизнь животного [11]. Наблюдалась слабо позитивная корреляция между возрастом первого отёла и удоем за лактацию у помесных молочных коров в Эфиопии [12].…”
unclassified